I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Petrology of Peter I Øy (Peter I Island), West Antarctica - Prestvik, Tore; Barnes, Calvin G; Sundvoll, Bjørn; Duncan, Robert A (Journal of volcanology and geothermal research, 1990)
Peter I Øy is located in the Bellinghausen Sea, 400 km NE of Thurston Island, West Antarctica. It is a Pleistocene volcanic island situated adjacent to a former tranform fault on the continental rise of the presently passive margin between the Pacific and Antarctica. New K-Ar age determinations ranging from 0.1 to 0.35 Ma show that the volcanism responsible for this island took place at the same time as post-subduction, rift-related volcanism occurred in the nearby Marie Byrd Land and the Antarctic Peninsula. The rocks of the island are alkalic basalt and hawaiite, benmoreite and trachyte. The basic tocks typically contain phenocrysts of olivine (Fo61–84), diopsidic augite, and plagioclase (ca. An60). Small xenoliths are present and consist of mantle-type spinel lherzolite, cumulate clinopyroxenite and gabbro and felsic inclusions that consist of medium-grained strained quartz, plagioclase, and abundant colorless glass. Chemically, the basic rocks are characterized by rather high MgO (7.8–10.2 wt.%) and TiO2 (3.1–3.7 wt.%) and relatively low CaO (8.4–9.5 wt.%) contents. They have steep REE patterns, [(La/Yb)N = 20] with HREE only 5 x chrondrite. Y and Sc are almost constant at relatively low levels. Compatible trace elements such as Ni and Cr show considerable variation (190–300 and 150–470 ppm, respectively.), whereas V shows only little variation. Sr and Nd isotope ratios vary slightly with 87Sr/86Sr averaging 0.70388 and 143Nd/144Nd 0.512782, both typical for ocean island volcanism. Lead isotope ratios are consistently high in basalts; 206Pb/204Pb = 19.194, 207Pb/204Pb = 15.728 and 208Pb/204Pb = 39.290, whereas benmoreïte is somewhat less radiogenic. Oxygen isotope analyses average ‰ . Incompatible trace elements vary by a factor of 1.5–2.0 within the range of the basic rocks. It is proposed that the incompatible trace-element variations represent different degrees (<10%) of partial melting, and that these melts were later modified by minor ( ‰ ) olivine and spinel fractionation. The very small variation in Y (and Sc) and the very fractionated REE pattern indicate that the source had an Y- and HREE-rich residual phase, most probably garnet. Furthermore, it is suggested that the source was slightly hydrous and that melting took place at 18–20 kbar. Trachyte was derived by multiphase fractionation of ne-normative basalts, and benmoreite from hy-normative parental liquids. The rocks of Peter I Øy are generally of the same type and age as those outcropping in extensional regimes on the nearby continent, and therefore, these occurrences may be related to each other in some way. However, the Peter I Øy rocks are considerably more radiogenic in strontium and less radiogenic in neodymium than the rocks of the Antarctic Peninsula and Marie Byrd Land. Possible explanations are that Peter I Øy represent asthenospheric hot spot activity, or transtensional rifting as subduction ceased.
Keywords: Peter I. Øy; geologi; petrologi

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene